Cardiac performance is influenced by rotational changes of position in the transversal plane, both in the horizontal and in the 60̊ head‐up postures. (26th April 2018) - Kölegård, Roger; Da Silva, Cristina; Siebenmann, Christoph; Keramidas, Michail E.; Eiken, Ola
Summary: Background: Echocardiography is usually performed with the subject/patient lying in the left lateral position (LLP), because the acoustic window is better in this than in the supine position (SP). The aim was to investigate cardiac responses to rotational changes of position in the transversal plane, from SP to LLP while horizontal, and from leaning on the back (HUT‐LB) to leaning on the left side (HUT‐LL) while tilted 60° head‐up from the horizontal. Methods: Healthy men ( n  = 12) underwent 10‐min HUT provocations. Cardiac variables were measured using two‐dimensional echocardiography, Doppler, tissue Doppler imaging and arterial pressures using a volume‐clamp method. Results: In horizontal posture, cardiac volumes were smaller in SP than in LLP: end‐diastolic volume (EDV) by 14%, end‐systolic volume (ESV) by 13%, stroke volume (SV) by 14%, and cardiac output (CO) by 16% ( P <0·03). In addition, the mitral annular plane systolic excursion (MAPSE) was 11% smaller ( P  = 0·001) and the left ventricle isovolumic relaxation time (IVRT) 27% longer in SP than in LLP. The ejection fraction, heart rate, arterial pressure and pulmonary ventilation were similar in SP and LLP. During HUT, EDV, SV, CO and MAPSE were smaller, and IVRT was longer, in HUT‐LB than in HUT‐LL, by −19%, −20%, −17%, −18% and +35%, respectively ( P <0·04). Conclusions: Cardiac performance is enhanced in LLP versus SP and in HUT‐LL versus HUT‐LB, which can be attributed to improved venous return, conceivably, wholly or in part, due to increased hydrostatic pressure gradients between the caval veins and the heart in the LLP and HUT‐LL positions.